'A touchy subject': teaching and learning about difference in the religious education classroom. Issue 1 (2nd January 2020) - O'Grady, Kevin; Jackson, Robert
ABSTRACT: The present article reports research conducted during 2018 in a secondary school in South Yorkshire, England with a class of 11–12-year-old boys and girls and the class teacher of religious education (RE), in consultation with the head and deputy head of the RE faculty. The focus of the project was on the extent to which existing research findings can assist teachers to deal with issues of religious diversity, including how the classroom can be a 'safe space' for dialogue and discussion and how media influences can be managed. It was one of a number of projects conducted by members of the Signposts International Research Network, who have undertaken independent studies in the UK, Norway and Sweden, which address issues identified in the Council of Europe publication Signposts . The findings reported in the present article highlight: the need for teachers to be given support in learning skills for managing classroom dialogue; the interest of young people in exploring difference; and the benefits of participation in classroom-based collaborative research.